2003
DOI: 10.2807/esm.08.09.00424-en
|View full text |Cite
|
Sign up to set email alerts
|

The internet, a simple and convenient tool in Chlamydia trachomatis screening of young people

Abstract: The objective of this study was to evaluate a new C. trachomatis screening method based on a home sampling strategy and using the internet as a facility for the participants to obtain their test results. A population based screening study was designed in primary care setting in Umeå, Sweden. It included all males aged 22 years (n=1074), living in Umeå, a city with 100 000 inhabitants. The participation rate was 38.5%. In the study group, 1.1% were infected with C. trachomatis. Participants obtained their resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 0 publications
3
24
1
Order By: Relevance
“…Of the 110 patients contacted, less than 40% were recruited to the study. In keeping with similar studies, however (21,25), once committed to the study, withdrawal rates were relatively low with 78% of all patients completing this study. It is assumed that as the burden of a study increases, the completion rate of a study decreases and this may reflect the personal circumstances and level of motivation of the participants.…”
Section: Limitationssupporting
confidence: 79%
See 1 more Smart Citation
“…Of the 110 patients contacted, less than 40% were recruited to the study. In keeping with similar studies, however (21,25), once committed to the study, withdrawal rates were relatively low with 78% of all patients completing this study. It is assumed that as the burden of a study increases, the completion rate of a study decreases and this may reflect the personal circumstances and level of motivation of the participants.…”
Section: Limitationssupporting
confidence: 79%
“…We believe that the differences in the nutrient data between week zero and week two may be the result of patients reading the computer screen more accurately and becoming more aware of the expectations of the website by their subsequent visits (learning effect) (21,22). This can be seen by the changes in the variability (SD) of the nutrient data between week zero and week two as no dietary advice had been provided at these timepoints.…”
Section: Repeatabilitymentioning
confidence: 99%
“…1. While research designs unique to the Internet have yet to emerge, investigators have shown that it is feasible to conduct surveys for HIV/STD prevention in surveillance (Novak, Edman, Jonsson, & Karlsson, 2003), randomized controlled trials Bull et al, 2004), and quantitative, qualitative, and mixed method studies online Ross, 2005). Further, by building to the strengths of the Internet, researchers are advancing HIV prevention survey research in some interesting ways (as will be outlined below).…”
Section: Testing Theorymentioning
confidence: 96%
“…Only recent large studies of active screening using home-collected specimens have included men. [12][13][14][15]62,123,124 Findings from both qualitative interviews and quantitative questionnaires in the ClaSS project suggest that men and women reacted differently to being invited to take part in chlamydia screening, being tested and receiving a positive diagnosis. Response rates were lower among men than women in this study and in other studies.…”
Section: Gender and Chlamydia Screeningmentioning
confidence: 99%